Clinical, thermographic, and tensiometric evaluation of rat cutaneous wounds treated with collagen gel associated with F18 bioactive glass - da Silva, Bruna Martins [UNESP]; Dos Santos, Ivan Felismino Charas [UNESP]; Mancuso, Paula [UNESP]; Pereira, Letícia Albuquerque Fortes [UNESP]; Moroz, Ivan [UNESP]; Gallina, Marina Frazatti [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Souza, Marina Trevelin; Pellizzon, Claudia Helena [UNESP]; Júnior, José Ivaldo Siqueira Silva [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Alves, Liandra Amara Garcia (FapUNIFESP (SciELO), 2024)
Purpose: To evaluate the association of collagen gel with F18 bioactive glass (BG) in the healing of non-contaminated cutaneous wounds induced in healthy Wistar rats. Methods: One hundred twelve adult and healthy Wistar rats were randomly divided into four groups (n = 28): saline solution (0.9%); healing ointment based on allantoin and zinc oxide; collagen gel; and association of F18 BG powder and collagen gel. All the rats underwent the creation of a 3-cm diameter wound in their dorsal region. Macroscopic, thermographic, and tensiometric evaluations of the wound were performed. Results: The presence of granulation tissue varied significantly in and between the groups. The surface temperature assessed through thermography of wounds treated with saline solution (0.9%) increased significantly over time and between the groups. No difference was identified regarding tensiometry. Conclusion: Collagen gel associated with F18 BG induced beneficial healing effects on non-contaminated cutaneous wounds in Wistar rats, which included the induction of increased blood perfusion as assessed through thermography.
Keywords: Biocompatible Materials; Collagen; Materials Testing; Skin; Wound Healing